Hubungan Massa Lemak Tubuh dan Kadar Estradiol Serum pada Wanita Premenopouse di Kota Padang - Virna Zufti Pratiwi; Ulya Uti Fasrini; Yuniar Lestari (Jurnal Ilmu Kesehatan Indonesia, 2021)
Background. Premenopause is a transition period from reproduction to menopause. This phase is characterized by a decrease in estradiol levels which causes body fat mass and cholesterol levels tend to rise in most women of premenopausal age. Objective. This study aims to determine the relationship of body fat mass and cholesterol levels with serum estradiol levels in premenopausal women in Padang city. Method. This study is an analytic study witha cross sectional study design. This study involved 112 data of premenopausal female respondents aged 40-55 years in the city of Padang, which consisted of data on age, occupation, body fat mass, total cholesterol levels and estradiol levels. Data obtained from observation of the master table. Analysis of the relationship of body fat mass and cholesterol levels with estradiol levels was using the One Way Anova test. Result. The results showed the mean body fat mass of premenopausal women in Padang City was 37.3±7.2%, the mean cholesterol level was 204.45±40.73 mg/dL and the average estradiol level was 145.72±49.82 pg/ml. Based on the results of the analasis test, a significant negative correlation was obtained, p=0.026 (p<0.05) between cholesterol levels with estradiol levels. While there is no relationship between body fat mass with estradiol levels p=0.714 (p>0.05). Conclusion. There is a relationship between cholesterol levels with estradiol levels, but there is no relationship between body fat mass with serum estradiol levels of premenopausal women in Padang City.